Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Audit Pada Kantor Akuntan Publik di Batam - Cibanis Mei Kristin Nazara; Viola Syukrina E Janrosl (LPPM Universitas Putera Batam, 2023)
This study aims to analyze the effect of audit independence, competence and professional ethics on audit quality. In this study, a sample of 65 respondents were those who worked and as employees of several KAP in Batam City. Multiple regression tests are used to test hypotheses in order to analyze the influence of factors on audit quality. This study shows that independence and competence do not have a positive effect on audit quality. At the same time, audit ethics has a significant positive impact or influence on audit quality.